The Impact of Curcumin, Gingerol, Piperine, and Proanthocyanidin on the Oxidative Stability of Sunflower and Soybean Oils for Developing Bio-Lubricants - Diana-Luciana Cursaru; Dănuța Matei (Lubricants)
Vegetable oils can serve as a fundamental raw material for formulating lubricants due to their exceptional lubricating properties, which are indicated by viscosity indexes greater than 100. Vegetable oils, due to their unsaturated fatty acids with one or more double bonds, have two significant drawbacks: low oxidation stability and poor performance in low temperatures. The oxidative stability of sunflower and soybean oils was evaluated and correlated with the unsaturation degree calculated based on fatty acid profiles. Different percentages of piperine, curcumin, gingerol, and proanthocyanidin (0.5, 1, 2, and 3 wt.%) have been tested as potential bio-additives for sunflower and soybean oils. All four bio-additives have been observed to enhance oxidation resistance, with gingerol being the most effective, followed by curcumin, piperine, and proanthocyanidin. Bio-additives’ effectiveness increases when applied to bio-oils with lower degrees of unsaturation, such as soybean oil. Adding gingerol significantly enhances the induction period, increasing it by about 10 times for soybean oil and 6 times for sunflower oil. This suggests that gingerol can effectively prolong the induction period of both oils.